The global emerging market : strategic management and economics - Kvint, V. L. (New York : Routledge, 2009)
This academic book is the ideal guide for current business leaders and students on how to make strategic, symmetric, and asymmetric time-sensitive decisions related to the GEM. Its also a culmination of 45years of professional life above the artic circle in Siberia.
Includes bibliographical references (p. [440]-442) and index.
aia 07/05/13
Loan.
Keywords: International business enterprises; Globalization-economic aspects; Strategic planning; Developing countries